OP0200 Characteristics and outcomes of prospectively reported pregnancies exposed to certolizumab pegol from a safety database. (12th June 2018) - Clowse, M.E.B.; Scheuerle, A.E.; Chambers, C.; Afzali, A.; Kimball, A.; Cush, J.J.; Cooney, M.; Shaughnessy, L.; Vanderkelen, M.; Förger, F.
Abstract : Background: Anti-tumour necrosis factor medications (anti-TNFs) are effective in controlling chronic inflammatory diseases, but information about their use and safety in pregnancy is limited. Consequently, anti-TNFs are often discontinued early in gestation. Certolizumab pegol (CZP), an Fc-free, PEGylated anti-TNF approved for treatment of rheumatic diseases and/or Crohn's disease, has no active placental transfer. Objectives: This project provides information on pregnancy outcomes in women receiving CZP, especially those with early pregnancy exposure. Methods: Prospective and retrospective data on maternal CZP exposure, including timing and duration, outcomes, comorbidities, and major malformations were extracted from the UCB Pharma safety database through 6 March 2017. This analysis was limited to prospective reports to avoid bias associated with retrospective submissions. Numbers of live births, miscarriages, elective abortions, stillbirths, and major congenital malformations were ascertained. Results: From a total of 1541 maternal CZP-exposed pregnancies, 1137 were reported prospectively, of which 528 pregnancies (including 10 twin pregnancies) had 538 known outcomes: 459 live births (85%), 47 miscarriages (9%), 27 elective abortions (5%), and 5 stillbirths (1%) (figure 1). Of the 459 live births, 8 (2%) cases of major congenital malformations were reported (vesicoureteral reflux, club foot, congenital heart disease, cerebral ventricle dilatation, polydactyly, anal fistula, accessory auricle, and hydronephrosis). Of the 528 prospective pregnancies with known outcomes, 436 (83%) were exposed during the 1 st trimester, when most organogenesis occurs; 201 pregnancies were exposed during the entire pregnancy. Conclusions: This analysis represents the largest published cohort of pregnant women exposed to an anti-TNF for management of chronic inflammatory diseases. Analysis of pregnancy outcomes does not indicate a malformative effect of CZP compared to the EU general population (2%–3%), nor an increased risk of foetal death. These data are reassuring for women of childbearing age considering treatment with CZP; however, the ongoing collection of post-marketing surveillance data, including the ongoing MotherToBaby study from the Organisation of Teratology Information Specialists, will provide further important information. Acknowledgements: This study was funded by UCB Pharma. The authors thank the patients and their caregivers in addition to the investigators and their teams who contributed to this study. Editorial services were provided by Costello Medical. All costs associated with development of this abstract were funded by UCB Pharma. Disclosure of Interest: M. Clowse Grant/research support from: Pfizer and Janssen, Consultant for: UCB Pharma, A. Scheuerle Grant/research support from: UCB Pharma, INC Research and Genentech, C. Chambers Grant/research support from: AbbVie, Amgen Inc., Bristol-Myers Squibb, Celgene, GlaxoSmithKline, Janssen, Pfizer, Hoffman-La Roche, Genentech, Genzyme Sanofi-Aventis, Seqirus, Takeda and UCB Pharma, A. Afzali Grant/research support from: UCB Pharma, Consultant for: UCB Pharma, AbbVie, Takeda and IBD Horizons, A. Kimball Consultant for: UCB Pharma, Dermira, Janssen and AbbVie, J. Cush Grant/research support from: Pfizer, Janssen, AbbVie, Celgene, Novartis, AstraZeneca and Genentech, Consultant for: Janssen, AbbVie, Novartis, Amgen, Genentech, Lilly and Horizon, M. Cooney Employee of: UCB Pharma, L. Shaughnessy Employee of: UCB Pharma, M. Vanderkelen Employee of: UCB Pharma, F. Förger Grant/research support from: UCB Pharma, Speakers bureau: Mepha, Roche and UCB Pharma